Analysis of the Alignment of Bank Nusa Tenggara Barat Syariah's Core Values 'AMANAH' with the Principles of Maqashid Syariah - Muhammad Harfin Zuhdi; Abdul Malik; Baiq El Nadriati (Lembaga Bale Literasi, 2026)
This study aims to reframe the core value of trust in Islamic banking through the perspective of maqashid al-sharia with a case study on Bank NTB Syariah. The approach used is qualitative with a descriptive-analytical design and an interpretive paradigm. Data were obtained through the analysis of internal documents and the review of relevant scientific literature. The analysis technique used was thematic analysis combined with the framework of maqashid al-sharia. The results of the study show that trust is not only interpreted as trust in transactions, but as a holistic principle that includes moral, social, and spiritual responsibility. The implementation of trust has been realized in governance, services, human resource management, and supervisory mechanisms, although there is still a gap between normative values and empirical reality. Therefore, an integrative model of trust is needed as a sustainable strategy for Islamic banking that connects the spiritual, governance, social, and economic dimensions, while strengthening public trust and institutional competitiveness. These findings also affirm the importance of leadership with integrity, strengthening organizational culture, and an ethics-based evaluation system to ensure that the internalization of trust runs consistently and has a real impact on the performance, reputation, and sustainability of Islamic financial institutions in an optimal sustainable manner.